Redrawing the frontiers in the age of post-publication review - Galbraith, David W. (Frontiers in Genetics, 2015)
Publication forms the core structure supporting the development and transmission of scientific knowledge. For this reason, it is essential that the highest standards of quality control be maintained, in particular to ensure that the information being transmitted allows reproducible replication of the described experiments, and that the interpretation of the results is sound. Quality control has traditionally involved editorial decisions based on anonymous pre-publication peer review. Post-publication review of individual articles took the lesser role since it did not feed directly back to the original literature. Rapid advances in computer and communications technologies over the last thirty years have revolutionized scientific publication, and the role and scope of post-publication review has greatly expanded. This perspective examines the ways in which pre- and post-publication peer review influence the scientific literature, and in particular how they might best be redrawn to deal with the twin problems of scientific non-reproducibility and fraud increasingly encountered at the frontiers of science.